The integrative role of parenting styles and parental involvement in young children’s science problem-solving skills - Lin, Xunyi; Yang, Weipeng; Xie, Wanlin; Li, Hui (Frontiers in Psychology, 2023)
Introduction: How parents encourage and engage young children to learn science and solve scientific problems remains an understudied issue. Parenting styles have been widely studied and found to be associated with children’s various developmental outcomes. However, there is a dearth of research linking parenting styles to early science skills which build from both cognitive and social abilities. This cross-sectional study intended to pilot test a mediation model of parental involvement in the relationship between parenting styles and children’s science problem-solving skills. Methods: A total of 226 children (M = 62.10 months, SD = 4.14, 108 girls) and their parents was recruited from five kindergartens in Fuzhou in China by adopting stratified random sampling. All parents completed the Demographics Questionnaire, the Parenting Style and Dimension Questionnaire, and the Chinese Early Parental Involvement Scale. Each child was tested with the Picture Problem Solving Task. Pearson’s correlation analysis and intermediary effect analysis were conducted using IBM SPSS 25 in data analysis. Results and Discussion: Parental involvement had a significant mediating effect in the bidirectional associations between parenting styles and children’s science problem-solving skills. The findings suggested that children with higher science problem-solving skills were likely to be raised by parents who were employing a flexible (i.e., authoritative) parenting style and had more involvement in children’s formal and informal learning environments, while children’s higher levels of science problem-solving skills predicted a higher level of parental involvement and a more flexible parenting style.